An unusual manifestation of olfactory neuroblastoma. (13th March 2018) - Batacchi, Zona; Andeen, Nicole K; Trikudanathan, Subbulaxmi
Abstract : A 62-year-old woman presented with an 11-month history of worsening nasal symptoms of rhinorrhoea, anosmia, nasal congestion and intermittent epistaxis. MRI revealed a large mass in the upper nasal vault. Biopsy of the mass revealed an olfactory neuroblastoma. While waiting resection, she acutely developed severe proximal muscle weakness, lethargy and lower extremity oedema. Blood glucose was elevated, and hypokalaemic metabolic alkalosis was noted. Elevated serum cortisol level of 95.7 µg/dL (8.7–22.4 µg/dL) and markedly elevated 24-hour urinary cortisol level of 6962.3 µg/24 hours (4.0–50.0 µg/24 hours) with concurrent adrenocorticotropic hormone (ACTH) level of 171 pg/mL (6–58 pg/mL) were suggestive of an ACTH-dependent source of hypercortisolism. A subsequent positive high-dose dexamethasone suppression test was consistent with ectopic ACTH production. She underwent near-total resection of the right nasal mass followed by radiotherapy, resulting in complete resolution of signs and symptoms of cortisol excess.